Designing a Green-School Education Model of Community Development in Rural Areas - Windiasih, Rili; Suswanto, Bambang; Sabiq, Ahmad; Sulaiman, Adhi Iman; Prasetiyo, Prasetiyo (Technium Social Sciences Journal, 2022)
Education is an important factor in developing human resources as development actors take advantage of the potential of natural, social, and economic resources in rural areas in the form of green schools. The purpose of this research is to design a model of green-school education as community development in rural areas. The research used Participatory Learning and Action (PLA) with direct observation, analysis of documentation, open interviews, and Focus Group Discussions (FGD). Determination of research locations at the "Green Kids" School educational institutions in Sokaraja and the Baturaden Green School of Banyumas Regency, Central Java of Indonesia. Research informants were determined by purposive sampling consisting of foundation administrators, teachers or teachers and students, educational leaders, educational activists or activists, experts, and educational practitioners. The research analysis uses verification analysis and data triangulation to reduce, classify and design models. The results (1) Education can be designed with a curriculum based on the natural, social and cultural potential of the community in the form of a green school institution. (2) Green-School is very important in utilizing, preserving, and developing the potential of natural resources such as agriculture, animal husbandry, fisheries, plantations, and forestry which are the uniqueness and advantages of rural communities.